(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This article explores the concepts of water and fire in the English linguistic landscape and their profound influence on idioms, metaphors and symbolic language. As the main elements of nature, water and fire are deeply embedded in English expressions, reflecting their important roles in human life and culture